Determinants of the Financing Structure of the Acquiring Companies in the Pre-Merger Period. Results of the Research - Ilona Fałat-Kilijańska; Jana Glaserova; Piotr Luty; Milena Otavova (Nauki o Finansach)
The article's main objective is to identify the factors influencing the financing structure and capital changes in the pre-merger periods in the acquiring companies. The authors examined the relations between various industries and different size companies. Based on the analyses, it can be concluded that in small companies, the explanatory variables identified based on the literature review were statistically insignificant in many periods (in fact almost all). Completely different behaviour was observed in the group of large companies, where the same set of explanatory variables was statistically significant. The result of the research on the existence of non-linear relationships between company parameters is that in the case of some variables, there is no question of a linear nature of dependence. The study analysed the five years preceding the mergers of 307 business entities. The source of the survey data was the database prepared by the company InfoCredit SA for the Accountants Association in Poland. The authors used Statistica software and inductive reasoning for the study - supported by Spearman's rank correlation analysis, linear and polynomial regression analysis, and variable scatter analysis.(original abstract)